Evaluasi Perubahan Iklim dan Pengaruhnya terhadap Pola Tanam, Waktu Tanam serta Produktivitas Kedelai (Glycine max L. Merrill) Di Kabupaten Malang Jawa Timur - Ninuk Herlina; S. Fajriani; F. A. Rahman (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Herlina et al, 2018. The Evaluation of Climate Change and The Effect to Cropping Pattern, Panting Season and Productivity of Soybean (Glycine max L. Merrill) in Malang Regency, East Java. JSLO 7(2):106-120.Â Climate change is a negative impact due to development activities on Earth. Forests that lose function caused degradation and increases in greenhouse gas concentrations cause global warming and trigger climate change. Climate change is thought to affect cropping pattern, planting time and soybean productivity. The purpose of the study was to evaluate the expected climate change and analyze correlation between climatic elements and the pattern and time of planting and soybean productivity. The research was carried out in March to April 2018 in Kalipare, Donomulyo, Singosari and Dau, Malang Regency, East Java. The tool used is a questionnaire. The material are the climate elements, soybean productivity and interview data. This study uses survey research methods. Total respondents were 40 farmers. Climate change analysis by analyzing mean changes in temperature, rainfall and number of rainy days in period 1 (1988-1997), period 2 (1998-2007) and period 3 (2008-2017). Correlation coefficient analysis is used to determine the correlation between climatic elements and soybean productivity and followed by t test. The results show that climate change has occurred in Malang Regency for the past 30 years. The correlation between temperature, rainfall with soybean productivity showed a